Metal organic frameworks as promising sensing tools for electrochemical detection of persistent heavy metal ions from water matrices: A concise review. (March 2023) - Shafqat, Syed Salman; Rizwan, Muhammad; Batool, Maria; Shafqat, Syed Rizwan; Mustafa, Ghulam; Rasheed, Tahir; Zafar, Muhammad Nadeem
Abstract: Water bodies are being polluted rapidly by disposal of toxic chemicals with their huge entrance into drinking water supply chain. Among these pollutants, heavy metal ions (HMIs) are the most challenging one due to their non-biodegradability, toxicity, and ability to biologically hoard in ecological systems, thus posing a foremost danger to human health. This can be addressed by robust, sensitive, selective, and reliable sensing of metal ions which can be achieved by Metal organic frameworks (MOF) based electrochemical sensors. In the present era, MOFs have caught greater interest in a variety of applications including sensing of hazardous pollutants such as heavy metal ions. So, in this review article, types, synthesis and working mechanism of MOF based sensors is explained to give general overview with updated literature. First time, detailed study is done for sensing of metal ions such as chromium, mercury, zinc, copper, manganese, palladium, lead, iron, cadmium and lanthanide by MOFs based electrochemical sensors. The use of MOFs as electrochemical sensors has attractive success story along with some challenges of the area. Considering these challenges, we attempted to highlight the milestone achieved and shortcomings along with future prospective of the MOFs for employing it in electrochemical sensing devices for HMIs. Finally, challenges and future prospects have been discussed to promote the development of MOFs-based sensors in future. Graphical abstract: Image 1 Highlights: MOF as electrochemical sensing systems. Various synthetic approaches for synthesizing MOFs sensing materials. Landscape view for the sensing of different heavy metals. Challenges and detection mechanism of MOFs based sensors.